Preparation method of aqueous zinc ion battery negative electrode coating material
By using porous carbon nitride-loaded nano zinc oxide negative coating materials in aqueous zinc ion batteries, the problems of battery electrochemical stability and cycle life are solved, and higher specific capacity retention and longer service life are achieved.
Patent Information
- Application Number
- CN202411950011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
The poor electrochemical stability and unsatisfactory cycle life of aqueous zinc ion batteries are mainly due to dendrite growth, surface passivation, by-product formation and corrosion on the negative electrode side.
The nano-zinc oxide negative electrode coating material is used to dissolve nano-zinc oxide and porous carbon nitride through ultrasonic to form a composite material, and coat it on the surface of the zinc foil with this material, providing rich zinc deposition active sites and inhibit dendrites' growth and corrosion.
It significantly improves the specific capacity retention rate and cycle life of aqueous zinc ion batteries, enhances the mechanical properties and chemical stability of the batteries, and extends the service life of the batteries.
Smart Images

Figure HDA0005214638340000011 
Figure HDA0005214638340000012 
Figure HDA0005214638340000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aqueous zinc ion batteries, and the present invention relates to a method for preparing a negative electrode coating material for aqueous zinc ion batteries, and specifically to a method for preparing a porous carbon nitride-loaded nano zinc oxide negative electrode coating material and its application. Background Art
[0002] The rapid development of wearable electronics and electric vehicles has stimulated the growing demand for exploring new energy storage systems, while lithium-ion batteries are mainly concerned with limited energy density and potential safety issues. In this regard, aqueous multivalent ion batteries hold great promise due to their high energy supply through multiple electron transfers and the use of aqueous electrolytes. The theoretical specific capacity of Zn (5855 mAh cm -3 ) exceeds the theoretical specific capacity of lithium metal (2061 mAh cm -3 ), in addition, Zn has a high redox potential (-0.76V relative to the standard hydrogen electrode). Other advantages of Zn also involve non-flammability, low cost and high safety, all of which are particularly beneficial for practical wearable technology. Although significant progress has been made in the exploration of zinc storage materials and devices so far, the main bottleneck hindering the large-scale utilization of systems based on aqueous zinc metal is poor electrochemical stability and unsatisfactory cycle life, which mainly stems from dendrite growth, surface passivation, byproduct formation and corrosion on the negative electrode side. The solution to these problems is of great significance for the design of stable aqueous zinc-ion batteries. Researchers have developed many improvement strategies to improve the electrochemical performance of batteries, such as zinc surface structural modification, alloying modification, preparation of interface coatings, etc. In the past, the coating materials used were mostly polymers, precious metals, rare earth materials, etc. These materials all have different problems, such as complex preparation process and high recycling cost for polymers, and scarcity of precious metals and rare earth materials. Compared with other coating materials, simple inorganic materials have the characteristics of simple preparation, high safety, low cost, simple process and scalable production, which has attracted the interest of many researchers. The chemical deposition method is used to make zinc oxide adhere to the bare zinc surface. This method has many defects, such as uneven adhesion, weak adhesion, high difficulty in operation and difficulty in controlling the loading capacity. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, the present invention aims to solve the problems of zinc dendrite growth, zinc negative electrode surface corrosion, uneven surface deposition, etc., and provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery. The raw materials for the preparation are easy to obtain and the operation is simple. The impedance of the assembled symmetrical battery is significantly reduced, the half-cell cycle efficiency stability is significantly improved, and the service life of the aqueous zinc ion battery is improved.
[0004] The above object of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a negative electrode coating material for an aqueous zinc ion battery comprises the following steps:
[0006] (1) Grind urea into powder by ball milling twice.
[0007] (2) The powder is placed in a tube furnace for heat treatment to obtain a yellow solid powder.
[0008] (3) The yellow solid powder and nano zinc oxide (ZnO) were dissolved in 50 ml of deionized water in a mass ratio of 5:2, ultrasonicated for 2 hours, filtered, and washed with deionized water and anhydrous ethanol for 2-3 times respectively; placed in a vacuum drying oven and dried for 24 hours to obtain a light yellow solid powder.
[0009] (4) The light yellow solid powder and polyvinylidene fluoride (PVDF) are uniformly mixed in a mass ratio of 7:1, and 22-25 drops of N-methylpyrrolidone (NMP) are added and stirred to form a coating.
[0010] (5) The coating is applied to the surface of the zinc foil using a simple scraping method.
[0011] Furthermore, in step (1), the ball milling conditions are: rotation speed of 150-170 r / min; ball milling time of 20 min.
[0012] Furthermore, in step (2), the specific sintering conditions of the tube furnace heat treatment are: a heating rate of 2.3°C / min, a calcination temperature of 550°C, a calcination time of 30 minutes; and an argon atmosphere.
[0013] Furthermore, in step (3), the vacuum drying temperature condition is 50°C.
[0014] The present invention also requests to protect the application of the aqueous zinc ion battery negative electrode coating material prepared by the above preparation method in preparing the negative electrode of the aqueous zinc ion battery, specifically using a coating machine to evenly coat the prepared coating material on a metal zinc foil.
[0015] The invention provides a coating material and a simple coating method for preparing porous carbon nitride by loading active substance nano zinc oxide. A protective layer is coated on zinc foil to modify the interface properties of zinc negative electrode. When used as aqueous zinc ion battery, the battery capacity and cycle stability are significantly improved.
[0016] The present invention first prepares porous carbon nitride by a simple thermal synthesis method, uses the material as a carrier to load zinc oxide to prepare a porous carbon nitride loaded nano zinc oxide negative electrode coating material, and uses the material as a water-based zinc ion battery negative electrode coating material to modify the negative electrode interface. The porous carbon nitride loaded nano zinc oxide negative electrode coating material prepared by the present invention is used as a water-based zinc ion battery negative electrode interface coating, provides abundant zinc deposition active sites, induces uniform deposition of zinc ions, absorbs free hydrogen ions in the electrolyte, inhibits hydrogen evolution reaction, increases the interface impedance between the obtained electrode material and the electrolyte, is conducive to isolating the corrosion of the electrolyte to the negative electrode, and improves the cycle stability of the assembled battery.
[0017] The beneficial effects of the present invention compared with the prior art are:
[0018] (1) The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery. The porous carbon nitride-loaded nano-zinc oxide negative electrode coating material is coated on the surface of a metal zinc foil to provide abundant zinc deposition active sites, thereby enabling zinc ions to be deposited more evenly, thereby inhibiting the growth of zinc dendrites and improving the specific capacity retention rate and cycle life of the aqueous zinc ion battery. The negative electrode material prepared from the porous carbon nitride-loaded nano-zinc oxide negative electrode coating material can stably cycle 700 times in an aqueous zinc ion half-cell test and can be applied to the negative electrode of an aqueous zinc ion battery.
[0019] (2) The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery, using a porous carbon nitride-supported nano zinc oxide negative electrode coating material as a zinc negative electrode coating. The material has strong mechanical properties and excellent chemical stability, does not dissolve in an electrolyte, and does not react chemically with the electrolyte, and can isolate the zinc negative electrode surface from direct contact with the electrolyte, thereby inhibiting corrosion of the zinc surface by the electrolyte.
[0020] (3) The present invention provides a method for preparing a coating material for an aqueous zinc ion battery negative electrode, which uses urea and zinc oxide, which are readily available raw materials, to prepare the coating material, thereby solving the problems of environmentally unfriendly materials, complex processes, and difficult storage of products in the previous aqueous zinc ion battery negative electrode modification process. The preparation cost is low, the process is environmentally friendly, and the production is easy to operate. In the prior art, zinc oxide, sulfur-doped zinc oxide, and aluminum-doped zinc oxide negative electrodes are used as coating materials. Zinc oxide, sulfur-doped zinc oxide, and aluminum-doped zinc oxide have poor structural stability, poor chemical stability, and are not easy to form a stable coating, and the stabilization effect is lower than that of the material of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 100 times (such as Figure 1 a) and 500 times (such as Figure 1 b) Surface morphology of ZnO / CN@Zn prepared in Example 1 of the present invention under an optical microscope.
[0022] Figure 2 The contact angle of ZnO / CN@Zn prepared in Example 1 ( Figure 2 a) The contact angle of Bare Zn prepared in Comparative Example 1 (e.g. Figure 2 b) Comparison chart.
[0023] Figure 3 This is a comparison chart of half-cell efficiency-cycle number of ZnO / CN@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.
[0024] Figure 4 This is a comparison chart of the symmetrical battery impedance of ZnO / CN@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.
[0025] Figure 5 This is a comparison chart of the symmetrical battery impedances of ZnO / CN@Zn prepared in Example 1, Bare Zn prepared in Comparative Example 1, and ZnO@Zn prepared in Comparative Example 3.
[0026] Figure 6 This is a comparison chart of half-cell efficiency-cycle number of ZnO / CN@Zn prepared in Example 1, Bare Zn prepared in Comparative Example 1, and CN@Zn prepared in Comparative Example 2.
[0027] Figure 7 This is a comparison chart of the symmetrical battery impedances of ZnO / CN@Zn prepared in Example 1, Bare Zn prepared in Comparative Example 1, and ZnO@Zn-10 prepared in Comparative Example 4.
[0028] Figure 8 This is a comparison chart of half-cell efficiency-cycle number of ZnO / CN@Zn prepared in Example 1, Bare Zn prepared in Comparative Example 1, and CMC-ZnO / CN@Zn prepared in Comparative Example 5. DETAILED DESCRIPTION
[0029] The present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels. The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery. A porous carbon nitride-loaded nano zinc oxide negative electrode coating material is provided, and the negative electrode material for an aqueous zinc ion battery is prepared with the material. The negative electrode coating material for an aqueous zinc ion battery is coated on the surface of a metal zinc foil using a porous carbon nitride-loaded nano zinc oxide composite material, providing abundant active sites, so that zinc ions can be deposited more evenly and the growth of zinc dendrites can be inhibited; and the material has excellent mechanical strength and chemical stability, which effectively inhibits the corrosion of the electrolyte to the negative electrode; the raw materials for preparing the protective layer are easy to obtain and the operation is simple, the impedance of the assembled symmetrical battery is significantly reduced, the half-battery cycle efficiency stability is significantly improved, and the service life of the aqueous zinc ion battery is improved.
[0030] Example 1
[0031] A method for preparing a negative electrode coating material for an aqueous zinc ion battery,
[0032] (1) Grind urea into fine powder and obtain powder A by ball milling for multiple times;
[0033] (2) Powder A was placed in a covered porcelain boat and heated to 550°C in a tube furnace at a heating rate of 2.3°C / min for 4 hours. The mixture was calcined for 30 minutes and cooled to room temperature to obtain a yellow solid powder named CN.
[0034] (3) CN and nano zinc oxide (ZnO) were dissolved in 50 ml of deionized water in a mass ratio of 5:2, ultrasonicated for 2 hours, filtered, and washed with deionized water and anhydrous ethanol for 2-3 times respectively; placed in a vacuum drying oven and dried for 24 hours to obtain a light yellow solid powder named ZnO / CN.
[0035] (4) The light yellow solid powder and polyvinylidene fluoride (PVDF) are uniformly mixed in a mass ratio of 7:1, and 22-25 drops of N-methylpyrrolidone (NMP) are added and stirred to form a coating material.
[0036] (5) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named ZnO / CN@Zn.
[0037] Comparative Example 1
[0038] The metal zinc foil is not treated in any way and is named Bare Zn.
[0039] Comparative Example 2
[0040] (1) Grind urea into fine powder and obtain powder A by ball milling for multiple times;
[0041] (2) Powder A was placed in a covered porcelain boat and heated to 550°C in a tube furnace at a heating rate of 2.3°C / min for 4 hours. The mixture was calcined for 30 minutes and cooled to room temperature to obtain a yellow solid powder named CN.
[0042] (3) CN and polyvinylidene fluoride (PVDF) are uniformly mixed in a mass ratio of 5:1, and 22-25 drops of N-methylpyrrolidone (NMP) are added and stirred to prepare a coating material.
[0043] (4) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named CN@Zn.
[0044] Comparative Example 3
[0045] (1) Nano zinc oxide (ZnO) and polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 5:1, and 22-25 drops of N-methylpyrrolidone (NMP) are added and stirred into the coating material.
[0046] (2) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named ZnO@Zn.
[0047] Comparative Example 4
[0048] (1) Grind urea into fine powder and obtain powder A by ball milling for multiple times;
[0049] (2) Powder A was placed in a covered porcelain boat and heated to 550°C in a tube furnace at a heating rate of 2.3°C / min for 4 hours. The mixture was calcined for 30 minutes and cooled to room temperature to obtain a yellow solid powder named CN.
[0050] (3) CN and nano zinc oxide (ZnO) were dissolved in 50 ml of deionized water in a mass ratio of 5:1, ultrasonicated for 2 hours, filtered, and washed with deionized water and anhydrous ethanol for 2-3 times respectively; placed in a vacuum drying oven and dried for 24 hours to obtain a light yellow solid powder named ZnO / CN.
[0051] (4) The light yellow solid powder and polyvinylidene fluoride (PVDF) are uniformly mixed in a mass ratio of 6:1, and 22-25 drops of N-methylpyrrolidone (NMP) are added and stirred to form a coating material.
[0052] (4) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named ZnO / CN@Zn-10.
[0053] Comparative Example 5
[0054] (1) Grind urea into fine powder and obtain powder A by ball milling for multiple times;
[0055] (2) Powder A was placed in a covered porcelain boat and heated to 550°C in a tube furnace at a heating rate of 2.3°C / min for 4 hours. The mixture was calcined for 30 minutes and cooled to room temperature to obtain a yellow solid powder named CN.
[0056] (3) CN and nano zinc oxide (ZnO) were dissolved in 50 ml of deionized water in a mass ratio of 5:2, ultrasonicated for 2 hours, filtered, and washed with deionized water and anhydrous ethanol for 2-3 times respectively; placed in a vacuum drying oven and dried for 24 hours to obtain a light yellow solid powder named ZnO / CN.
[0057] (4) ZnO / CN and hydroxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 70:1, and 22-25 drops of ultrapure water were added to stir to form a coating.
[0058] (5) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named CMC-ZnO / CN@Zn.
[0059] Application Example 1
[0060] The ZnO / CN@Zn prepared in Example 1 was assembled into an aqueous zinc ion half-cell, wherein the positive electrode material was copper foil, the negative electrode material was ZnO / CN@Zn prepared in Example 1, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution. Test conditions: at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 Half-cell test was performed under the condition.
[0061] The ZnO / CN@Zn prepared in Example 1 was assembled into an aqueous zinc ion symmetrical battery, wherein the positive electrode material was the ZnO / CN@Zn prepared in Example 1, the negative electrode material was the ZnO / CN@Zn prepared in Example 1, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.
[0062] Test results: attached Figure 3 The ZnO / CN@Zn assembled half-cell prepared in Example 1 was charged at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 Under the test, it stably cycled for 700 times and the CE was stable at around 94%, showing excellent zinc plating / stripping recoverability. The stability of this coating material for aqueous zinc-ion batteries is significantly better than the existing technology.
[0063] The ZnO / CN@Zn prepared in Example 1 and the Bare Zn prepared in Comparative Example 1 were assembled into symmetrical cells and impedance tests were performed. Figure 4It can be seen that the impedance value of ZnO / CN@Zn prepared in Example 1 is 110Ω, which is much smaller than the impedance value of Bare Zn prepared in Comparative Example 1.
[0064] ZnO / CN@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1 were respectively -1 Contact angle measurement with zinc sulfate solution. Figure 2 It can be seen that the contact angle of ZnO / CN@Zn prepared in Example 1 is 121.7°, which is much larger than the contact angle of Bare Zn prepared in Comparative Example 1, showing an excellent hydrolysis effect on zinc sulfate electrolyte.
[0065] Application Comparative Example 1
[0066] The bare Zn prepared in comparative example 1 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was bare Zn prepared in comparative example 1, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .
[0067] The bare Zn prepared in comparative example 1 was assembled into an aqueous zinc ion symmetric battery, wherein the positive electrode was the bare Zn prepared in comparative example 1, the negative electrode was the bare Zn prepared in comparative example 1, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.
[0068] Test results: attached Figure 3 It can be seen that the bare Zn assembled half-cell prepared in Comparative Example 1 can only stably cycle 40 cycles, and after 40 cycles, the CE fluctuates greatly and short circuits occur. Figure 4 It can be seen that the impedance value of the symmetrical battery assembled with Bare Zn prepared in Comparative Example 1 is 890Ω.
[0069] Application Comparative Example 2
[0070] The CN@Zn prepared in Comparative Example 2 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was CN@Zn prepared in Comparative Example 2, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .
[0071] Test results: attached Figure 6It can be seen that the CN@Zn assembled half-cell prepared in Comparative Example 2 can only stably cycle 307 times, the CE fluctuates greatly, and a short circuit occurs at 307 cycles.
[0072] Application Comparative Example 3
[0073] The ZnO@Zn prepared in Comparative Example 3 was assembled into an aqueous zinc ion symmetrical battery, wherein the positive electrode material was the ZnO@Zn prepared in Comparative Example 3, the negative electrode material was the ZnO@Zn prepared in Comparative Example 3, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.
[0074] Attached Figure 5 It can be seen that the impedance of the symmetrical battery assembled with ZnO@Zn prepared in Comparative Example 3 is 497Ω, which is much greater than that of ZnO / CN@Zn prepared in Example 1.
[0075] Application Comparative Example 4
[0076] The ZnO / CN@Zn-10 prepared in Comparative Example 4 was assembled into an aqueous zinc ion symmetrical battery, wherein the positive electrode material was the ZnO / CN@Zn-10 prepared in Comparative Example 4, the negative electrode material was the ZnO / CN@Zn-10 prepared in Comparative Example 4, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.
[0077] Attached Figure 7 It can be seen that the impedance of the symmetrical battery assembled with ZnO / CN@Zn-10 prepared in Comparative Example 4 is 510Ω, which is much larger than that of ZnO / CN@Zn prepared in Example 1, and the ion transmission efficiency is poor.
[0078] Application Comparative Example 5
[0079] The CMC-ZnO / CN@Zn prepared in Comparative Example 5 was assembled into an aqueous zinc ion half-cell, wherein the positive electrode material was copper foil, the negative electrode material was CMC-ZnO / CN@Zn prepared in Comparative Example 5, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.
[0080] Test results: attached Figure 8 It can be seen that the half-cell assembled with CMC-ZnO / CN@Zn prepared in comparative example 5 can only stably cycle 271 times, while the half-cell assembled with ZnO / CN@Zn electrode material prepared in example 1 can stably cycle 700 times.
[0081] The present invention provides a method for preparing a porous carbon nitride loaded nano zinc oxide negative electrode coating material, and the negative electrode coating material is used as a negative electrode coating for an aqueous zinc ion battery. The negative electrode coating material for an aqueous zinc ion battery is coated on the surface of a metal zinc foil using a ZnO / CN composite material. ZnO is a fine powder, which has poor adhesion as a coating, is chemically unstable and easily soluble in an electrolyte, and also reacts with the electrolyte. Therefore, selecting a carrier with stable chemical properties to load zinc oxide is a hot research direction at present. The porous carbon nitride loaded nano zinc oxide composite material (ZnO / CN) prepared by loading nano zinc oxide on porous carbon nitride has high mechanical strength and stable chemical properties, is insoluble in the electrolyte and does not react with the electrolyte, isolates the electrolyte from direct contact with the zinc negative electrode surface, and reduces the corrosion of the electrolyte on the zinc negative electrode surface. The porous structure of the material can increase the diffusion layer for zinc ion deposition, and nano zinc oxide can effectively induce zinc ion deposition, thereby inhibiting the formation of zinc dendrites. The raw materials for preparing the protective layer are easy to obtain and the operation is simple. The impedance of the assembled symmetrical battery is significantly reduced, and the stability of the half-cell cycle efficiency is significantly improved, thereby improving the service life of the aqueous zinc-ion battery.
[0082] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a negative electrode coating material for an aqueous zinc ion battery, characterized in that: The following steps are involved: (1) Grind urea into powder by ball milling twice; (2) heat-treating the powder in a tube furnace to obtain a yellow solid powder; (3) Dissolve the yellow solid powder and nano zinc oxide in 50 ml of deionized water in a mass ratio of 5:2, perform ultrasonication for 2 hours, filter, wash with deionized water and anhydrous ethanol 2-3 times respectively; place in a vacuum drying oven and dry for 24 hours to obtain a light yellow solid powder; (4) Mix the light yellow solid powder and polyvinylidene fluoride in a mass ratio of 7:1, add 22-25 drops of N-methylpyrrolidone and stir to form a coating; (5) The coating is applied to the surface of the zinc foil using a simple scraping method.
2. The method for preparing a negative electrode coating material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the ball milling conditions are: rotation speed of 150-170 r / min; ball milling time of 20 min.
3. The method for preparing a negative electrode coating material for an aqueous zinc ion battery according to claim 1, wherein: In step (2), the specific sintering conditions of the tube furnace heat treatment are: heating rate of 2.3°C / min, calcination temperature of 550°C, calcination time of 30 minutes; and atmosphere of argon.
4. The method for preparing a negative electrode coating material for an aqueous zinc ion battery according to claim 1, wherein: In step (3), the vacuum drying temperature condition is 50°C.
5. Application of the aqueous zinc ion battery negative electrode coating material prepared by the preparation method according to any one of claims 1 to 4 in preparing the negative electrode of an aqueous zinc ion battery, characterized in that: The prepared coating material is evenly coated on the metal zinc foil using a coating machine.